2004
DOI: 10.1136/sti.2003.005454
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis in the United Kingdom: a systematic review and analysis of prevalence studies

Abstract: Objectives: To undertake a systematic review to obtain estimates of genital Chlamydia trachomatis prevalence in various populations in the United Kingdom and Ireland; to determine which populations have the highest rates of infection; and to explore the most important determinants of infection. Methods: Electronic databases were searched using the keywords ''chlamydia'' and ''England,'' ''Wales,'' ''UK,'' ''Scotland,'' ''Ireland,'' or ''Britain.'' Additional unpublished data and references were solicited from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
126
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(150 citation statements)
references
References 52 publications
15
126
0
8
Order By: Relevance
“…The C. trachomatis positivity rate of 9.9% for the study population, which was recruited from patients at a genitourinary medicine clinic, is consistent with that reported previously for the United Kingdom (1). Although all the quantitative data for organism load analyzed in the present study were obtained with a QLCR assay, the QLCR data for a subset of samples were found to be highly correlated with corresponding QPCR results.…”
Section: Discussionsupporting
confidence: 67%
“…The C. trachomatis positivity rate of 9.9% for the study population, which was recruited from patients at a genitourinary medicine clinic, is consistent with that reported previously for the United Kingdom (1). Although all the quantitative data for organism load analyzed in the present study were obtained with a QLCR assay, the QLCR data for a subset of samples were found to be highly correlated with corresponding QPCR results.…”
Section: Discussionsupporting
confidence: 67%
“…Para N. gonorrhoeae, los estudios de población reportan prevalencias de 0,08 a 2,6 % (1,3). La variabilidad en las frecuencias está determinada por las características sociodemográficas y los hábitos sexuales de la población estudiada, así como por los métodos diagnósticos usados, entre otros factores (5).…”
unclassified
“…A pesar de la elevada heterogeneidad en la ocurrencia de la infección, puede evidenciarse que en diversas poblaciones de comunidad general o clínicas, hasta 20% puede resultar infectado; esto corrobora la necesidad de la tamización, el diagnóstico oportuno y el tratamiento precoz, para disminuir la recurrencia de este infección y sus consecuencias clínicas; máxime al tener presente que la variabilidad en la magnitud de la infección no depende del tipo de prueba diagnóstica ni la muestra empleada 11 . …”
Section: Discussionunclassified
“…Finalmente, dicho estudio no halló diferencias según el tipo de prueba diagnóstica, muestra clínica ni año de realización 11 .…”
Section: Artículo Originalunclassified
See 1 more Smart Citation